2019
DOI: 10.1021/acsomega.9b00784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyamine Binding on the Stability of DNA i-Motif Structures

Abstract: B-form DNA can adopt alternative structures under conditions such as superhelical duress. Alternative DNA structures are favored when there is asymmetric distribution of guanosine and cytosine on complimentary DNA strands. A guanosine-rich strand can form a four-stranded structure known as a quadruplex (G4). The complimentary cytosine-rich strand can utilize intercalating cytosine–cytosine base pairing to form a four-stranded structure known as the i-motif (iM). Both secondary structures are energetically uphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Besides, the compound 3i had moderate Δ T m values (7.0 °C, Table 1 ). It has been reported that the polyamines could stabilize DNA secondary structures [ 34 , 35 ]. The significantly higher ΔT m values of 3c than the other derivatives promoted us to investigate whether the polyamine side chain (1,5,8,12-tetraazadodecane) of 3c could stabilize Py24 individually.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the compound 3i had moderate Δ T m values (7.0 °C, Table 1 ). It has been reported that the polyamines could stabilize DNA secondary structures [ 34 , 35 ]. The significantly higher ΔT m values of 3c than the other derivatives promoted us to investigate whether the polyamine side chain (1,5,8,12-tetraazadodecane) of 3c could stabilize Py24 individually.…”
Section: Resultsmentioning
confidence: 99%
“…Uranium also seems to have an effect on polyamine metabolism, involving different metabolites such as spermidine (F0) and L-methionine (F1), spermine and finally arginine (F1, F2) [ 58 ]. Polyamines are involved in many processes which are essential for cell growth, DNA double helix stabilization and cationic transporters [ 59 , 60 , 61 , 62 , 63 ]. For example, arginine is known to be involved in the anti-inflammatory process, but also, in the sperm motility [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lane d in agarose gel electrophoresis and no migration of free DNA indicating that most of the DNA was captured by the nanoparticles because of the high affinity of spermine to the DNA. 20 Indeed, it is known that a strong electrostatic interaction exists between the phosphate groups of DNA and the amino groups of spermine, as well as hydrophobic and hydrogen bonds. 21 Nanoparticles stability and nucleic acid protection are important parameters for efficient nucleic acid delivery.…”
Section: Discussionmentioning
confidence: 99%